TEACHERS EFFORTS TO IMPROVE STUDENTS' LEARNING OUTCOMES BY USING IMAGES IN CHRISTIAN RELIGIOUS EDUCATION AND CHARACTERISTICS - Mariati Tondang (Jurnal Scientia, 2022)
Teacher's Efforts to Improve Student Learning Outcomes by using Picture Media in Christian Religion and Morals Education Subjects Class V Public Elementary School 060908 in the Even Semester Materials for the Holy Spirit My Helper in the 2018/2019 Academic Year The aim of this research is to improve student learning outcomes in Class V SD Negeri 060908 Medan for the 2018/2019 academic year. The method used in this research is the Classroom Action Research Method using 2 cycles, the subjects of this research are students of class V SD Negeri 060908 Medan as many as 16 people, the instrument used to obtain data is by using tests, observing the range of values ​​for the test is Value highest and lowest . The instrument used for data processing is to calculate the number of students' scores that have not reached the KKM and the scores that have reached the KKM. The KKM has been determined, namely 70. The results of this study indicate that there is an increase in learning outcomes using the Role Playing Method with the following results: (1) In Cycle I, students get the highest score of 85, the lowest score of 44 Average score of 64.5 Then (2) in the second cycle increased to the highest score of 95 The lowest score of 70, the average value of 82.5.